Artventure 1982 : A Royal Bank program of juried exhibitions and awards for outstanding Ontario Art students. - Belshaw Beatty, Linda; The Art Gallery at Harbourfront, Toronto (Toronto : The Royal Bank of Canada, 1982)
Ciraco, Vito ; Cockburn, Sue ; Cripps, Andrew ; Desrosiers, Pierre ; Eddy, Christopher ; Graner, Ruth ; Kembry, Nancy ; Kliorikaitis, Anna ; Kokoska, Mary Ann ; Lee, Susan ; Matri, Anat ; Panko, Marla ; Toth, Paul ; Van Goch, Flora ; Wong, Ying
Artventure 1982 : A Royal Bank program of juried exhibitions and awards for outstanding Ontario Art students, The Art Gallery at Harbourfront, Toronto, August 4 to 22, 1982
English
kunstcatalogus